Análise da conexão de geradores eólicos duplamente alimentados com compensação série - Massing, Jorge Rodrigo (2008)
This dissertation addresses the main problems related to doubly-fed induction generators (DFIG) connection to grids with unbalanced voltages. Series compensation is used to achieve balanced voltage on the stator of the machine, avoiding torque oscillations and high currents due to the grid voltage unbalance. The DC-link voltage control proposed reduces the complexity of the converter when compared to the alternatives considered in the literature. The close to no-load operation of the DFIG is also depicted. Simulation results for a commercial large scale generator are presented to demonstrate the performance of the system with the proposed controller.